Compatibility of timber and non-timber forest product management in natural tropical forests: perspectives, challenges, and opportunities - Guariguata, Manuel R.; García Fernandez, C.; Sheil, Douglas; Nasi, Robert; Herrero-Jáuregui, C.; Cronkleton, P.; Ingram, V.J. (2010)
Tropical forests could satisfy multiple demands for goods and services both for present and future generations. Yet integrated approaches to natural forest management remain elusive across the tropics. In this paper we examine one combination of uses: selective harvesting of timber and non-timber forest product (NTFP) extraction. We analyze the current status of this combination and speculate on prospects and challenges regarding: (i) resource inventory, (ii) ecology and silviculture, (iii) conflict in the use of multipurpose tree species, (iv) wildlife conservation and use, (v) tenure, and (vi) product certification. Our conclusions remain preliminary due to the relative paucity of published studies and lessons learned on what has worked and what has not in the context of integrated management for timber and NTFPs. We propose at least three ways where further research is merited. One, in improving ‘opportunistic’ situations driven by selective timber harvesting that also enhance NTFP values. Two, to explicitly enhance both timber and NTFP values through targeted management interventions. Three, to explicitly assess biophysical, social, regulatory and institutional aspects so that combined benefits are maximized. Interventions for enhancing the compatibility of timber and NTFP extractionmust be scaled in relation to the size of the area being managed, applied timber harvesting intensities, and the dynamics of multiactor, forest partnerships (e.g., between the private sector and local communities). In addition, training and education issuesmay have to be re-crafted with multiple-usemanagement approaches inserted into tropical forestry curricula. copyrigh 2009 Elsevier B.V.